An analysis of the cost of public secondary fishery education - Lina, Telesforo S. 1927- (1970)
The aim of the study is to determine the amount appropriated and expended for the operation and maintenance of public secondary fishery schools in the Philippines from the fiscal year 1959-1960 to 1968-1969 and to determine the desired cost of operation and maintenance of this type of vocational school during its first five years of operation.
Thesis (M.Ed.)--University of the Philippines
Typescript
Keywords: Fisheries as profession; Fisheries -- Philippines